2019
DOI: 10.3390/molecules24162884
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme Entrapment in Amphiphilic Myristyl-Phenylalanine Hydrogels

Abstract: Supramolecular amino acid and peptide hydrogels are functional materials with a wide range of applications, however, their ability to serve as matrices for enzyme entrapment have been rarely explored. Two amino acid conjugates were synthesized and explored for hydrogel formation. These hydrogels were characterized in terms of strength and morphology, and their ability to entrap enzymes while keeping them active and reusable was explored. It was found that the hydrogels were able to successfully entrap two comm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Hydrogels with good environmental response have attracted more and more attention in pharmaceuticals, medicine, tissue engineering, materials science, food, and agriculture [5,6,7,8,9,10]. In particular, pH- and salt-responsive hydrogels are mostly studied because both parameters are important environmental factors in physiological and chemical systems [11,12]. Hydrogels made from natural polymers, including chitin [13], gelatin [14], cellulose [15], and sodium alginate [16], have many unique advantages, such as good biocompatibility, biodegradability, and these natural polymers have abundant resources.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels with good environmental response have attracted more and more attention in pharmaceuticals, medicine, tissue engineering, materials science, food, and agriculture [5,6,7,8,9,10]. In particular, pH- and salt-responsive hydrogels are mostly studied because both parameters are important environmental factors in physiological and chemical systems [11,12]. Hydrogels made from natural polymers, including chitin [13], gelatin [14], cellulose [15], and sodium alginate [16], have many unique advantages, such as good biocompatibility, biodegradability, and these natural polymers have abundant resources.…”
Section: Introductionmentioning
confidence: 99%
“…Still, out of these prepared hydrogels, the gel at pH 7 showed the best thixotropic response with the excellent recovery of the moduli owing to its relatively lesser recovery time than other gels ( Figure 1 D, Table 1 ). The gel exhibited injectable properties, as shown in Figure 1 E. In the same year, Kraatz et al reported myristic acid (CH 3 (CH 2 ) 12 COOH)-capped L- and D-Phenylalanine (Phe) (AA3 and AA4, Figure 1 F), which are much more prone to form a hydrogel in a monobasic phosphate buffer at pH 7 [ 62 ]. Phe is a well-known aromatic hydrophobic amino acid that can readily undergo a self-assembly process within a network through hydrophobic and π-π interactions to form supramolecular gels [ 55 , 59 , 63 , 64 , 65 , 66 , 67 ].…”
Section: Amino Acid (Aa)-based Thixotropic Hydrogelmentioning
confidence: 97%
“…However, the fairly weak interaction with the target molecule is one of their limitations . To overcome this drawback, many researchers have investigated the effect of surface-modifying functional groups. , …”
Section: Introductionmentioning
confidence: 99%
“…15 To overcome this drawback, many researchers have investigated the effect of surface-modifying functional groups. 8,16 The use of conducting polymers such as polyaniline (PANI) either as biomolecule carriers 17 or surface modifiers 12,18 is extensively investigated. PANI is a relatively low-cost polymer, can be easily synthesized, has good stability to extreme temperatures and pH, and is also resistant to microbial attack.…”
Section: Introductionmentioning
confidence: 99%